Tobacco smoking and acute exercise on immune-inflammatory responses among relative short and longer smoking histories. (November 2019) - Hartmann, Tegan; Marino, Frank; Duffield, Rob
Abstract: This study examined the acute effects of combined tobacco smoking and exercise on immune-inflammatory responses in smoker populations with shorter or longer smoking history. The cohort comprised 14 young male adult (YSM) and 12 middle-aged (MSM) male active cigarette smokers matched for aerobic fitness and smoking behavior. Following an initial familiarization and baseline testing session, participants completed a smoking and exercise protocol. This protocol involved the inhalation of two cigarettes (12 mg tar, 1 mg nicotine) within 15 min, and following a 10 min recovery period, 40 min of cycling at 50% peak aerobic workload. Venous blood was obtained pre- and post-protocol for analysis of interleukin (IL)-6, IL-1receptor antagonist (ra), IL-1beta (β) and monocyte chemoattractant protein-1 (MCP-1) and total leukocyte count. There was no baseline differences between age groups for IL-6 or MCP-1 (p > 0.05), although higher basal IL-1ra was evident in YSM (p < 0.05). Further, no significant differences existed between groups for post-exercise IL-1ra or IL-6 responses; though MSM demonstrated an elevated MCP-1 at 4 h post (p < 0.05). No between-group differences for total leukocyte count, platelets, neutrophils, lymphocytes or monocytes (p > 0.05) were observed; although higher concentrations of basophils immediately post and 4 h post-exercise, and higher eosinophils at 4 h post-exercise were evident in MSM (p < 0.05). The current study highlights that prolonged elevations in MCP-1, alongside leukocytosis, accompany inhalation of tobacco smoke prior to exercise.